Air Pollution, Its Mortality Risk, and Economic Impacts in Tehran, Iran - V Brajer; J Hall; M Rahmatian (Tehran University of Medical Sciences, 2012)
Background: Air pollution in Tehran is widely recognized as a serious environmental challenge, posing significant threats to the health of the resident population. Improving air quality will be difficult for many reasons, including climate and topography, heavy dependence on motor vehicles for mobility, and limited resources to reduce polluting emissions. Consequently, it is useful to have information regarding the scale of the health threat and the economic value of reducing that threat. Methods: This paper integrates information on air quality, population, economic valuation, and health science to assess the most serious impact of fine particle pollution on humans, which is increased mortality risk, and provides estimates of the costs of present pollution levels, both in terms of risk and in terms of economic value relative to attaining air quality standards. Results: Mid-range results indicate that mortality risk for the population aged 30 and over would be reduced from 8.2 per 1,000 residents annually to 7.4 per 1,000 and that the estimated annual economic benefits of this reduced risk would be $378.5 million, if health-based World Health Organization-recommended annual average PM2.5 standards were met. Conclusions: The potential public health benefits of reducing particulate air pollution are significant, and will increase with growing population.